Growth, Mortality and Recruitment Patterns of Amblyrhynichthys truncatus (Bleeker) in Paya Bungor, Pahang - Ambak, Mohd Azmi (1984)
This paper attempts to determine the growth, mortality I1nd recruitment patterns of A'mblyrhynichthys uuncatus by using a computer-based methoa for the analysis of length-frequency data (ELEFAN I & II). It is shown that this species has an approximate life span of four years with -the following growth parameters; Loo=29.5cm, K=0.425 and - -0.41989. While natural mortality (M = 1.04) is comparable to other species in the lake, fishing mortality (F - 4.15) and exploitation rates are found to be relatively high. This fish is highly susceptible to trammel nets with full retention occurring at 18cm length while the mean length at first capture is 17.8cm. There appears to be a single recruitment season with a peak in January.